Research progress in medical imaging for intracranial aneurysms: technological advances in diagnosis, management, and clinical integration - Zhou, Yuwei; Weng, Wei (Frontiers in Neurology, 2025)
Intracranial aneurysms (IAs) represent a significant cerebrovascular disorder that has attracted considerable scrutiny due to the elevated rates of mortality and morbidity associated with their rupture. The ongoing evolution of medical imaging techniques has led to the emergence of non-invasive imaging options, including Computed Tomography Angiography (CTA), Magnetic Resonance Angiography (MRA), and Digital Subtraction Angiography (DSA). These modalities are essential for the early detection, risk evaluation, and therapeutic strategy formulation for IAs. Recently, the integration of artificial intelligence (AI) and three-dimensional (3D) reconstruction technologies has further improved the precision and efficiency of imaging diagnostics. This review provides a systematic assessment of advancements in imaging diagnostic methods for IAs, covering both established and novel imaging techniques, AI-enhanced diagnostics, hemodynamic evaluations, the role of imaging in treatment, and prospective development directions. The objective is to furnish thorough references for clinical diagnosis and investigation in this vital field of medicine.